Letter - Joint Emergency Committee, Cambridge, 7 May 1926 (Cambridge)
1926-05-07 "Letter - Joint Emergency Committee, Cambridge, 7 May 1926" [g0349001.jpg], 7 May 1926, Joint Emergency Committee, Cambridge Local Organisation